Interrupted aortic arch: A case report - Andrea Franconeri; Francesco Ballati; Maurizio Pin; Luisa Carone; Gian M Danesino; Adele Valentini (Indian Journal of Radiology and Imaging, 2020)
Interrupted aortic arch diagnosed in adult age is a rare entity, with only a few cases published in the literature. Most of them are classified as type A interrupted aortic arch and differential diagnosis is associated with severe chronic coarctation. We present a case of a 52-year-old woman accessed to the emergency department for chest and right upper limb pain that increased in the last days. She underwent a computed tomography angiogram showing interruption of the aortic arch, distal to left subclavian artery origin, large bilateral collateral vessels connecting subclavian arteries to descending aorta with multiple voluminous aneurysms, a bicuspid aortic valve, dilatated tubular segment of ascending thoracic aorta, and a suspected atrial septal defect. A nonsystematic literature review regarding these conditions has been performed.